Ethnobotany of the Gitksan Indians of British Columbia - Smith, Harlan I., 1872-1940.; Tarpent, Marie-Lucie, 1941-; Compton, Brian Douglas, 1958-; Rigsby, Bruce; Canadian Ethnology Service; Canadian Museum of Civilization (Hull, Quebec : Canadian Museum of Civilization, 1997)
During the 1920s Harlan I. Smith, an archaeologist with the National Museum of Canada, documented plant and animal knowledge and use among the Gitksan, Nuxalk and Ulkatcho Carrier of British Columbia. This volume is an edited version of a manuscript by Smith, which contains information on 112 botanical species and their traditional cultural roles among the Gitksan. Prepared between 1925 and 1927, Smith's work is the earliest, relatively comprehensive ethnobotanical study for any Tsimshianic group, the first record of a clearly ethnobotanical investigation undertaken in British Columbia, and the first to include the term "ethnobotany" in its title. This thoroughly revised version of the manuscript also offers additional introductory text, ethnobotanical and linguistic commentary, and concluding remarks not found in the original.
The Gitksan People, Their Language, and Their Homeland -- Botanical Environment of the Gitksan -- Brief Account of Harlan I. Smith's Activities at the National Museum Leading to the Production of "Ethno-botany of the Gitksan Indians of British Columbia" -- Smith's Original Manuscript. pt. 1. H.I. Smith's "Ethno-botany of the Gitksan Indians of British Columbia" pt. 2. The Gitksan Consultants and Smith's Research Methodology -- Additional H.I. Smith Materials on Gitksan Ethnobotany and the Kitwanga Garden of Native Plants. Transcription of the Gitksan Ethnobotanical Lexicon. Botanical Species Collected as Voucher Specimens or Observed and Noted by H.I. Smith. Plants and Fungi Known or Used by the Gitksan. Fungi (Mushrooms and Their Relatives). Lichens (Lichenized Fungi). Bryophytes (Mosses and Their Relatives). Pteridophytes (Ferns and Their Relatives). Gymnosperms (Conifers and the Taxad, Western Yew). Angiosperms (Flowering Plants), Dicotyledons.
Includes bibliographical references (pages 166-169) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Includes abstract in French.
Keywords: Gitxsan Indians -- Ethnobotany -- British Columbia; Ethnobotany -- British Columbia; Ethnobotany; Plants, Medicinal; Gitxsan -- Ethnobotanique -- Colombie-Britannique.; Ethnobotanique -- Colombie-Britannique.; Plantes médicinales.; Ethnobotany; British Columbia; Ethnobotanique -- Canada -- Colombie-Britannique.; Gitksan (Indiens) -- Ethnobotanique -- Canada -- Colombie-Britannique.